Simulation and study of the milling parameters on CuFeTaTiW multicomponent alloy - R. Martins; A.P.Gonçalves; J.B. Correia; A.Galatanu; E. Alves; M. Dias (Nuclear Materials and Energy, 2024)
The CuFeTaTiW multicomponent alloy has been devised as an interlayer thermal barrier in nuclear fusion reactors. In order to predict the phase constitution of this alloy, two different lines of work were performed: (a) simulation using Molecular dynamics and Monte Carlo and (b) study of the influence of mechanical alloying parameters on the structures formed. The simulation results show that the most stable structure is achieved starting from a bcc type-structure and using Monte Carlo simulation. In fact, in these conditions the separation into two bcc phases Fe-Ta-W and Cu-Ti is predicted at room temperature. However, the experimental preparation of the materials with mechanical alloying revealed that from 2 h of milling a single bcc phase is formed. The structure of the milled powder was not much influenced by the amount of the process control agent and the by the size of the W starting particles, but generally there was formation of Ta2H from the reaction between the powders and the process control agent.